White matter abnormalities in aneurysmal and angiographically negative subarachnoid hemorrhage: A diffusion kurtosis imaging study - Sara Khosdelazad; Harm J. van der Horn; Lieke S. Jorna; Rob J.M. Groen; Anouk van der Hoorn; Sandra E. Rakers; Anne M. Buunk; Jacoba M. Spikman (NeuroImage: Clinical, 2024)
Objective: Aneurysmal subarachnoid hemorrhage (aSAH) and angiographically negative subarachnoid hemorrhage (anSAH) cause an abrupt rise in intracranial pressure, resulting in shearing forces, causing damage to the white matter tracts. This study aims to investigate whole-brain white matter abnormalities with diffusion kurtosis imaging (DKI) after both aSAH and anSAH and explores whether these abnormalities are associated with impaired cognitive functioning. Methods: Five months post-ictus, 34 patients with aSAH, 24 patients with anSAH and 17 healthy controls (HC) underwent DKI MRI scanning and neuropsychological assessment (measuring verbal memory, psychomotor speed, executive control, and social cognition). Differences in DKI measures (fractional anisotropy, mean diffusivity, axial diffusivity [AD], radial diffusivity, and mean kurtosis) were examined using tract-based spatial statistics. Significant voxel masks were then correlated with neuropsychological scores. Results: All DKI measures differed significantly between patients with aSAH and HC, but no significant differences were found between patients with anSAH and HC. Although the two SAH groups did not differ significantly on all DKI parameters, effect sizes indicated that the anSAH group might be more similar to HC. Cognitive impairments were found for both SAH groups relative to HC. No significant associations were found between these impairments and white matter abnormalities in the aSAH group, but lower psychomotor speed scores were associated with higher AD values (r = -0.41, p = 0.04) in patients with anSAH. Conclusions: Patients with aSAH showed significant white matter diffusion abnormalities, while the anSAH group, despite cognitive deficits, did not. However, there were no significant differences between the SAH groups, and no correlations between DKI metrics and cognitive measures, except for one test on psychomotor speed in the anSAH group. Overall, this study suggests that while anSAH may not be as severe as aSAH, it is still not a benign condition. Further research with larger anSAH cohorts is necessary to gain a more precise understanding of white matter injuries, particularly regarding their prevalence.